Evolution of cities in Borneo: a kaleidoscope of urban landscapes for planning future resilient cities - Kozlowski, Marek; Ibrahim, Rahinah; Zaini, Khairul Hazmi (Emerald Group Publishing, 2021)
Purpose: This study aims to examine the trajectory of the urban growth of Borneo by portraying its resilient settlements in the pre-colonial times, tropical sensitive colonial architecture, the built environment of the post–independence period and finally the contemporary city image. This is followed by a comparative study of its major urban centres and determining how globalisation and neoliberalism impact the traditional urban settlements of this island and poses a threat to its rich biodiversity. Design/methodology/approach: This study uses case study research methodology involving selected cities on the Island of Borneo including Kota Kinabalu, Sandakan, Miri and Kuching (Sabah and Sarawak, Malaysia), Bandar Seri Begawan (Brunei), and major cities of the state of Kalimantan, Indonesia. Data collection includes a literature review, content analysis, field assessment and observations. The major research objectives would address past and current issues in the selected urban environment of Borneo. They address the historical evolution of major cities of Borneo, current urban development trends, the deterioration of the traditional urban fabric as a result of post–independence development and later globalisation. Findings: This study found that the rich cultural tradition and climate-responsive architecture from the past have been discontinued to pave way for fast track and often speculative development. The results contribute in the convergence of existing shortcomings of cities from three nations on Borneo Island in guiding future sustainable urban planning agenda for achieving a resilient city status while reinstating the character and the sense of place. The study expects the recommendations to become prerequisites for future urban planning in sensitive tropical regions. Originality/value: This research identified a new “Borneo approach” to urban development. The study strongly recommends top priorities for the central, state and local governments of Malaysia, Brunei and Indonesia allowing the planners and decision-makers to establish a new tropical urban planning initiative with the ample design practice for this unique region in Southeast Asia. The results of this study can serve as the guiding principles for other urban environments in fragile and sensitive tropical regions.